Peculiarity of Aesthetic Communications - Areška, Vitas (Problemos, 1986)
The article deals with the process of formation, manifestation and perception of objective artistic value. The interrelation between peculiarities of depicted phenomena arising in imagination and aesthetic impressions is not controlled and determined receptively. That’s why aesthetic emotions cannot change freely. The objectivization of individual aesthetic reactions must obtain the character of social aesthetic relations. That is why the focusing literary critique is necessary,